Lipid-coated nanocapillaries for DNA sensing - Hernández‐Ainsa, Silvia; Muus, Christoph; Bell, Nicholas A. W.; Steinbock, Lorenz J.; Thacker, Vivek V.; Keyser, Ulrich F. (The analyst, 2013)
We report a simple and efficient way to accomplish the chemical modification of glass nanopores by means of lipid self-assembly. Lipid coating improves the success rate of these glass nanopores as biosensors to detect λ-DNA.